Emotional Intensity and the Function of Imagery in Contemporary Popular Fiction - Sardevi Sardevi (Yayasan Kyadiren, 2025)
This study is grounded in the significance of stylistic inquiry for elucidating the role of imagery as a central component in constructing aesthetic experience in popular fiction, which has predominantly been examined from structural and adaptation-oriented perspectives. Drawing upon Nurgiyantoro’s classification of imagery into five categories—visual, auditory, kinesthetic, tactile, and olfactory—this research aims to identify and describe the types of imagery employed in *Dia Angkasa* by Nurwina Sari and to analyze their functions in shaping narrative atmosphere and reader experience. A descriptive qualitative design was applied, utilizing content analysis of the novel’s text. The findings reveal 176 instances of imagery, dominated by visual (70 instances) and kinesthetic (53 instances) forms, followed by auditory (39 instances), tactile (12 instances), and olfactory (2 instances). The analysis demonstrates that imagery constructs immersive atmosphere, reinforces characterization, and intensifies readers’ emotional engagement, confirming its strategic stylistic function in popular novels.